2013
DOI: 10.1089/neu.2012.2797
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stimulation of Transplanted Neurons Improves Motoneuron Survival, Axon Growth, and Muscle Reinnervation

Abstract: Few options exist for treatment of pervasive motoneuron death after spinal cord injury or in neurodegenerative diseases such as amyotrophic lateral sclerosis. Local transplantation of embryonic motoneurons into an axotomized peripheral nerve is a promising approach to arrest the atrophy of denervated muscles; however, muscle reinnervation is limited by poor motoneuron survival. The aim of the present study was to test whether acute electrical stimulation of transplanted embryonic neurons promotes motoneuron su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 86 publications
1
14
1
Order By: Relevance
“…6D). These results contrast with an earlier study in which we showed that motoneuron survival was increased when ventral cell preparations were stimulated at 20 Hz for 1 hour (96). Neural and glial progenitors were abundant in ventral cell preparations.…”
Section: Discussioncontrasting
confidence: 99%
“…6D). These results contrast with an earlier study in which we showed that motoneuron survival was increased when ventral cell preparations were stimulated at 20 Hz for 1 hour (96). Neural and glial progenitors were abundant in ventral cell preparations.…”
Section: Discussioncontrasting
confidence: 99%
“…The muscle atrophy was thereby alleviated. These observations were consistent with those of previous studies (Erb et al ., ; Yohn et al ., ; Casella et al ., ; Grumbles et al ., , ; Su et al ., ; Liu et al ., , ). When the grafted cells were removed and the residual distal stump was cross‐sutured to the proximal end of freshly cut ipsilateral common peroneal (CP) nerve, the axonal regeneration from the proximal stump of the injured CP nerve was promoted, and the muscle function was partially recovered.…”
Section: Discussionmentioning
confidence: 97%
“…59 Based on this cumulative evidence, one of the most successful stem cell transplant studies coupled brief electrical stimulation of the peripheral nerve with motor neuron cell grafts and demonstrated impressive cell survival and muscle re-innervation. 60 This landmark study suggests that the combination of regenerative cell therapies and artificial stimulation may be critical for achieving targeted plasticity and functional recovery following injuries or degeneration of the neuromuscular system.…”
Section: Successes In Regenerative Rehabilitation and Related Therapiesmentioning
confidence: 99%